Phoenix and The Carpet - Edith Nesbit
It was a big wooden box, and it had to be opened with a hammer and the kitchen poker; the long nails came squeaking out, and boards scrunched as they were wrenched off. Inside the box was soft paper, with beautiful Chinese patterns on it--blue and green and red and violet. And under the paper--well, almost everything lovely that you can think of. Everything of reasonable size, I mean; for, of course, there were no motors or flying machines or thoroughbred chargers. But there really was almost everything else. Everything that the children had always wanted--toys and games and books, and chocolate and candied cherries and paint-boxes and photographic cameras, and all the presents they had always wanted to give to father and mother and the Lamb, only they had never had the money for them. At the very bottom of the box was a tiny golden feather. No one saw it but Robert, and he picked it up and hid it in the breast of his jacket, which had been so often the nesting-place of the golden bird. When he went to bed the feather was gone. It was the last he ever saw of the Phoenix.